Pengaruh Resiliensi, Dukungan Sosial, dan Kesejahteraan Psikologis terhadap Kinerja Karyawan pada CV Duta Jaya Tehnic - Ahmad Agus Tri Mulyono; Miftahul Munir; Diana Ambarwati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines effects of resilience, social support, and psychological well-being on employee performance at CV Duta Jaya Tehnic. Resilience refers to an individual’s capacity to handle work pressure and challenges. Social support includes assistance from coworkers and family. Psychological well-being denotes a healthy mental state. The study proposed significant partial and joint effects for the three predictors. A quantitative survey design was used. Questionnaires were distributed to 38 employees. Multiple linear regression evaluated partial and joint relationships between predictors and performance. Results show a significant positive effect of resilience on performance (p = 0.001 < 0.05). Social support (p = 0.573) and psychological well-being (p = 0.700) show no significant partial effects. Jointly, the three predictors explain performance significantly (p < 0.001). The findings highlight a central role for personal resilience in improving performance at CV Duta Jaya Tehnic, while social support and psychological well-being show no standalone effect within this sample. Overall, the regression model with the three predictors provides meaningful explanatory power for employee performance in this company. Managerial implications follow from the evidence. Prioritize initiatives to build resilience, including brief coping-skill sessions, energy management, and recovery practices. Maintain support systems and well-being programs, yet direct resources first toward resilience building.